Resonant Scattering of Relativistic Outer Zone Electrons by Plasmaspheric Plume Electromagnetic Ion Cyclotron Waves - 苏振鹏 郑惠南 (Chinese physics letters, 2009)
The bounce-averaged Fokker-Planck equation is solved to study the relativistic electron phase space density （PSD） evolution in the outer radiation belt due to resonant interactions with plasmaspheric plume electromagnetic ion cyclotron （EMIC） waves. It is found that the PSDs of relativistic electrons can be depleted by 1-3 orders of magnitude in 5h, supporting the previous finding that resonant interactions with EMIC waves may account for the frequently observed relativistic electron flux dropouts in the outer radiation belt during the main phase of a storm. The significant precipitation loss of ~MeV electrons is primarily induced by the EMIC waves in H＋ and He＋ bands. The rapid remove of highly relativistic electrons （〉5MeV） is mainly driven by the EMIC waves in O＋ band at lower pitch-angles, as well as the EMIC waves in H＋ and He＋ bands at larger pitch-angles. Moreover, a stronger depletion of relativistic electrons is found to occur over a wider pitch angle range when EMIC waves are centering relatively higher in the band.